Association of physical activity and vitamin D deficiency with cognitive impairment in older adults: a population based cross-sectional analysis - Guo, Jing; Mo, Hongfei; Zuo, Longfei; Zhang, Xu (Frontiers in Nutrition, 2024)
The global aging situation is becoming increasingly critical and cognitive impairment in the elderly has become a public health burden of concern. Physical activity (PA) and vitamin D may play a key role in improving cognitive impairment.However, little studies have examined the interaction between these two. The purpose of this study was to assess the association of PA and vitamin D with cognitive impairment in older adults, as well as the interactions of PA and vitamin D.: This study was conducted by multi-stage random sampling of elderly people ≥60 years old, and a total sample of 2492 (1207 male and 1285 female, mean age of 69.41±6.75 years) with complete data was included in the analysis. PA was assessed by the Global Physical Activity Questionnaire, and <600 MET-min/wk was used as the division criteria. Serum vitamin D was measured by high-performance liquid chromatography tandem mass spectrometry, and 25-hydroxyvitamin D2/D3 concentration <20 ng/ml was used as a vitamin D deficiency criterion. Cognitive function was assessed by three subtests: the Consortium to Establish a Registry for Alzheimer's disease word learning test (CERAD-WL) for immediate and delayed learning, the Animal Fluency Test (AFT) for verbal fluency; and the Digit SymbolSubstitution Test (DSST) for information processing speed and switching attention. All three subtests were scored at less than the lowest quartile of the score as a criterion for cognitive impairment. Statistical analysis was performed using SPSS for chi-square test, rank sum test, interaction analysis, subgroup analysis and regression analysis.Results: Lower level of PA is associated with higher odds of cognitive impairment.